2022
DOI: 10.1016/j.str.2021.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the antibiotic darobactin modulating the β-barrel assembly factor BamA

Abstract: Highlights d Mechanical, kinetic, and energetic properties of BamA d Properties change upon binding to an antibiotic d Structural regions change mechanical stability and lifetime d Structural regions change free-energy and mechanical rigidity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 51 publications
(76 reference statements)
0
35
0
8
Order By: Relevance
“…Taken together, the different Darobactin-BamA binding interactions of Darobactin A, D9 and D22 likely reveal the structural basis for enhanced activity of engineered Darobactins, which are more closely paired with BamA to mimic the ß-sheet prolongation and to lock the BAM complex in the inactive state by sealing the lateral gate tightly (Figure 1, 3). [13] These structure and activity based findings are reinforced by the results of analyzing the different binding kinetics for Darobactin A, D9 and D22 revealing K D values of 0.278 µM, 0.3 µM and 0.159 µM, respectively (Figure S 43).…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…Taken together, the different Darobactin-BamA binding interactions of Darobactin A, D9 and D22 likely reveal the structural basis for enhanced activity of engineered Darobactins, which are more closely paired with BamA to mimic the ß-sheet prolongation and to lock the BAM complex in the inactive state by sealing the lateral gate tightly (Figure 1, 3). [13] These structure and activity based findings are reinforced by the results of analyzing the different binding kinetics for Darobactin A, D9 and D22 revealing K D values of 0.278 µM, 0.3 µM and 0.159 µM, respectively (Figure S 43).…”
Section: Resultsmentioning
confidence: 73%
“…Preceding Darobactin SAR studies focussed on native Darobactins [16,21] or were based upon observations from them. [19] Revealing the MoB of Darobactin A and D9 to BamA, combined with structural data of recently published Darobactins, [13,15,19,21] here enabled the first concise SAR study, in which we constructed twenty new derivatives, including twelve derivatives with terminal L-tryptophan exhibiting similar or better activity than Darobactin A (Figure S2). In our SAR study we found, that structural changes at position 6 and 7 appear to be the most important, necessary for interactions with β-hairpins of BamA, while the minor influence of position 4 on activity and BamA target interaction gives a valuable starting point for future structural modifications to further improve the pharmaceutical properties of Darobactins.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations